SGS-LTER avian road counts, breeding bird survey, on the Pawnee National Grassland in eastern Colorado, USA - Ryder, Ronald (Colorado State University. Libraries, 1968)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. The Breeding Bird Survey is a large-scale survey of North American birds. It is a roadside survey, primarily covering the continental United States and southern Canada, although survey routes have recently been initiated in Alaska and northern Mexico. The BBS was started in 1966, and the over 3,500 routes are surveyed in June by experienced birders. Routes 305, Nunn and 901, Rockport are located in the area of the SGS research site. The primary objective of the BBS has been the estimation of population change for songbirds. However, the data have many potential uses, and investigators have used the data to address a variety of research and management objectives. In the USGS-BBS Home Page, results from the BBS are summarized and pictures of birds and other species are information. Data from 1966-2002 were managed by the SGS-LTER project.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: grasslands; populations; population dynamics; biodiversity; animals; birds